The Role of Civil Society in the Overthrow of Omar Bashir’s Military Regime in Sudan - Miftahuddin (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
President Bashir’s military government has secured him to sit in the power for more than three decades since 1989. His strategy has allowed him to survive during many protest cycles. However, the 2018-19 protest has proved a different thing. In less than four months, the participation of Sudanese civil has successfully overthrown him from the power. What remains is that how this democratisation has succeeded and why? Who is behind the mobilisation of Sudanese civil power and how they mobilise people? This paper analyses the role of Sudanese Professional Association (SPA) in the process of Bashir’s fall during December 2018 and April 2019. Using Putnam’s social capital theory and descriptive qualitative analysis methods, this study suggests that the movement of SPA has succeeded in mobilising opposition parties, forcing Bashir’s security apparatus to announce the ending of his power. , confirming the trust as Putnam’s social capital suggested. Moreover, the Force of Freedom and Change (FFC) Alliance was also formed by the initiative of SPA, utilising their networking to mobilize people against Bashir.